1992
DOI: 10.1246/bcsj.65.858
|View full text |Cite
|
Sign up to set email alerts
|

Surface Adsorption and Micelle Formation of Dodecyltrimethylammonium Chloride and Dodecylammonium Chloride Mixture

Abstract: The miscibility of dodecyltrimethylammonium chloride (DTAC) and dodecylammonium chloride (DAC) in the adsorbed film at water/air interface and in the micelle was investigated by measuring the surface tension of the aqueous solution of surfactant mixture as a function of the total molality and composition of surfactants. The compositions of surfactants in the adsorbed film and micelle were evaluated by use of the thermodynamic equations developed previously. The results indicated that DTAC and DAC molecules mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…29 In fact, the phase diagrams for both systems are similar to those observed for mixtures of cationic surfactants having polar head groups of different sizes. [35][36][37] Hence, anesthetics with larger polar head groups may be said to be more geometrically favorable for the formation of spherical micelles than for surface adsorption at the plane interface. Here we assume that the influence of the hydrophobic aromatic rings of the anesthetic molecules is roughly similar to that of the methylene groups of the straight-chain surfactant, judging from the regularity of variation in Γ H vs m curves with X 2 .…”
Section: Resultsmentioning
confidence: 99%
“…29 In fact, the phase diagrams for both systems are similar to those observed for mixtures of cationic surfactants having polar head groups of different sizes. [35][36][37] Hence, anesthetics with larger polar head groups may be said to be more geometrically favorable for the formation of spherical micelles than for surface adsorption at the plane interface. Here we assume that the influence of the hydrophobic aromatic rings of the anesthetic molecules is roughly similar to that of the methylene groups of the straight-chain surfactant, judging from the regularity of variation in Γ H vs m curves with X 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The PDM of the DAC-TTAC system has a shape of a typical cigar type and reveals that the adsorbed film is enriched in trimethylammonium salts compared with the bulk solution and that the micelle is much more enriched than the adsorbed film similar to the DeAC-DTAC system as shown in previously [23]. In the DAC-DTAC system the micelle is much more enriched in trimethylammonium salts than the adsorbed film but less than the bulk solution [26]. As a result all the systems show that the micelle is enriched in trimethylammonium salts compared to the surface at the CMC.…”
Section: Resultsmentioning
confidence: 61%
“…Next we consider the miscibility of the DeAC-DTAC and DAC-DTAC systems [26]. The curves ofm vsX 2 ,m vsX H 2 , and ideal mixing are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the surfactant with the larger polar head and shorter hydrophobic chain is more abundant in the micelle component than in the adsorbed film in the binary mixtures of surfactant , Therefore, local anesthetics with larger polar head groups may geometrically favor interaction with globular structure compared with that with planar structure. Similarly, large difference between and values was observed for the DeAC−BC·HCl system although both values are negative except for the values in the high X 2 region.…”
Section: Discussionmentioning
confidence: 99%
“…48 In fact, the phase diagrams observed for mixtures of cationic surfactants having polar head groups of different sizes are similar to those obtained for both systems. 49,50 Therefore, local anesthetics with larger polar head groups may geometrically favor interaction with globular structure compared with that with planar structure. Similarly, large difference between X 2 M and X 2 H,C values was observed for the DeAC-BC‚HCl system although both values are negative except for the X 2 M values in the high X 2 region.…”
mentioning
confidence: 99%